2018
DOI: 10.1080/02614367.2018.1556724
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual model and research agenda for bidding, planning and delivering Major sport events that lever human rights

Abstract: In this conceptual paper, the authors propose a framework for how progressive human rights outcomes may be obtained in the context of bidding, planning and implementing major sport events (MSEs) through the implementation of four pathways, including good governance, the democratic participation of stakeholders, the formalisation of human rights agendas, and the deployment of sensitive urban development. The authors argue that there is a need for adherence to internationally recognised standards, such as the Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…While previous studies have explored the relationships between MSE hosting and human rights and the related ethical aspects, there is little research and managerial advice that has considered the role of advocacy organisations in leveraging these events to improve human rights outcomes. This is despite the fact that McGillivray et al (2019) have suggested that NGOs should be integrated into the bidding, planning and delivering MSEs from early on, to ensure "transparency and inclusiveness of the governance structure" (p. 184). In what follows, we explore the role of advocacy organisations in the context of MSEs.…”
Section: Human Rights Issues At Mega Sport Eventsmentioning
confidence: 99%
See 3 more Smart Citations
“…While previous studies have explored the relationships between MSE hosting and human rights and the related ethical aspects, there is little research and managerial advice that has considered the role of advocacy organisations in leveraging these events to improve human rights outcomes. This is despite the fact that McGillivray et al (2019) have suggested that NGOs should be integrated into the bidding, planning and delivering MSEs from early on, to ensure "transparency and inclusiveness of the governance structure" (p. 184). In what follows, we explore the role of advocacy organisations in the context of MSEs.…”
Section: Human Rights Issues At Mega Sport Eventsmentioning
confidence: 99%
“…Specific to the potential of MSEs to promote progressive human rights agendas, McGillivray et al (2019) proposed a conceptual framework highlighting a life-cycle approach to embedding human rights in the bidding, planning and delivery of MSEs. This model advocates that MSEs include "good governance, democratic participation of stakeholders, formalisation of human rights agendas and urban development for strengthening human rights" to realise their potential for positive social change (p. 185).…”
Section: Advocacy Organisations Mega Sport Events and Human Rights Promotionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other pillars of sustainability, such as the economic [92][93][94][95] or social sustainability [96][97][98][99][100][101][102][103], attract less individual attention, even though they are equally important to consider as the environmental issues because they are all interrelated. However, several studies consider these topics under the study approach of multisectoral legacies [3,14,19,22,[104][105][106][107][108][109][110][111][112][113][114][115][116][117][118][119][120], with "legacy" as one of the most important concepts in the conception of SMEs.…”
Section: Analysis Of the Literature On Sme And Sustainabilitymentioning
confidence: 99%